MENINGKATKAN KINERJA GURU MELALUI SUPERVISI PEMBELAJARAN - Ubabuddin (Ed-Humanistics : Jurnal Ilmu Pendidikan, 2019)
AbstractSupervision generally refers to efforts to improve the situation in the teaching and learningprocess. Because the main aspect is the teacher, the service and professional activities must bedirected towards efforts to improve the ability of teachers to manage teaching and learningactivities. Supervision is the effort of school stakeholders to lead teachers and other educationpersonnel, to improve teaching including stimulating, selecting growth and development ofteacher positions, selecting and revising educational goals, teaching materials, and teachingmethods and teaching evaluation. Supervision in schools is carried out by the principal who actsas a supervisor, so he must be able to carry out various supervision and controls to improveteacher performance. In supervising, a supervisor should pay attention to important things,namely: (1) The process of supervision/supervision covers two things, namely setting standardsfor the implementation of work and measuring the results/implementation of work, (2)information and supervision, including: ( a) supervision as an information system, (b) types ofmonitoring information, (c) system approach in supervision. (3) effective supervision is basedon effective management information systems, (4) program evaluation, namely makingjudgements according to an agreed and accountable set of criteria, (5) the principles ofsupervision with a partnership atmosphere, practical, systematic, objective, realistic, helpful,creative, anticipatory, constructive, and cooperative, (6) supervision targets can be concerningactivities or aspects supervised and those who do them.Keywords: Learning Supervision, Performance, Teacher